A new numerical method to solve nonlinear Volterra-Fredholm integro-differential equations - Hou, Jinjiao; Niu, Jing; Xu, Minqiang; Ngolo, Welreach (Mathematical Modelling and Analysis, 2021)
In this paper, a new method combining the simplified reproducing kernel method (SRKM) and the homotopy perturbation method (HPM) to solve the nonlinear Volterra-Fredholm integro-differential equations (V-FIDE) is proposed. Firstly the HPM can convert nonlinear problems into linear problems. After that we use the SRKM to solve the linear problems. Secondly, we prove the uniform convergence of the approximate solution. Finally, some numerical calculations are proposed to verify the effectiveness of the approach.